The Role of Community Health Workers in Developing Multidimensional Organizational Relationships. Issue 3 (July 2022) - Gronowski, Benjamin; Roth, Sarah E.; Woodson, Tanisha Tate; Cohen-Cline, Hannah; Kenton, Natalie
Abstract : Effective care coordination relies on organizations working collaboratively to meet medically and socially complex participants' needs. This study examines community health workers' (CHWs') roles in developing the organizational relationships on which care coordination efforts depend. Semistructured interviews (n = 13) were conducted with CHWs, CHWs' supervisors, and executive staff at organizations participating in a Washington State care coordination program. Interviewees described how CHWs developed and furthered multidimensional relationships in service of participants between and within participating organizations, as well as external organizations. Relationship-building challenges included COVID-19, geographic context, and staffing. The study concludes with considerations for care coordination efforts to support CHWs.